Canada's Potential Growth : Another Victim of the Crisis? - Estevao, Marcello; Tsounta, Evridiki (Washington, D.C. : International Monetary Fund, 2010)
This study investigates the impact of the current financial crisis on Canada's potential GDP growth. Using a simple accounting framework to decompose trend GDP growth into changes in capital, labor services and total factor productivity, we find a sizeable drop in Canadian potential growth in the short term. The estimated decline of about 1 percentage point originates from a sharply decelerating capital stock accumulation (as investment has dropped steeply) and a rising long-term unemployment rate (which would raise equilibrium unemployment rates). However, over the medium term, we expect Canada's potential GDP growth to gradually rise to around 2 percent, below the pre-crisis growth rate, mostly reflecting the effects of population aging and a secular decline in average working hours.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet